Grief During the Pandemic: The Experiences of Individuals Unable to Fulfill Their Religious and Cultural Rituals - Eylül Ceren Hekimoğlu; Münevver Zuhal Bilik; Sultan Berfin Uçurum; İrem Erten; Demet Can (Psikoloji Çalışmaları)
The COVID-19 pandemic has led to many deaths worldwide. Various restrictions and quarantines have been declared to control the number of deaths from the pandemic. Individuals have faced many changes in their daily and social lives due to these restrictions and quarantines. They have also been unable to fulfill their religious and cultural rituals following the experienced losses. The literature has discussed how performing religious and cultural rituals after a loss positively affects the mourning process. This research investigates how individuals in Turkish society who’ve suffered from loss due to COVID-19 during the pandemic but were unable to fulfill their religious and cultural rituals because of restrictions had experienced this process. For this purpose, semi-structured interviews were conducted with four participants between the ages of 45-65 who’d lost a relative due to COVID-19 in the last year. The interviews were analyzed using the interpretive phenomenological analysis. As a result, five major themes were created: negative emotions in the absence of rituals, attributions to rituals with respect to facilitating mourning, mechanisms for coping with loss, compensation for unfulfilled rituals, and being able to perform rituals despite restrictions. These themes have been interpreted from the Lacanian psychoanalytic perspective in the context of symbolic, imaginary, and real concepts. While the symbolic register involves the language, culture, and social environment, the imaginary involves the register in which the subject makes sense of reality in their inner world. Therefore, when considering the societal and cultural function of religious and cultural rituals, the participants had experienced a symbolic inadequacy in naming and accepting their loss. Instead, they tried to make sense of loss in the imaginary register while mourning. The alternative compensation methods the participants developed were interpreted as an effort to find a place for themselves in culture and society (i.e., in the symbolic order).